The Analysis of Islamic Law Maqosid on the Role of Women in Improving Family Welfare - Zeni Sunarti; Muhamad Hasan Sebyar (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
Abstract: The participation of women at work domain, does not only contributes in changing the mindset and economic structure of a region, but also has contributed greatly to family welfare. This research uses descriptive analysis method to analyze and describe the role of women in improving the economic welfare of the family in the perspective of maqashid syariah. Based on the results of the research, it is found that the implication is that the role of women is very positive in improving family welfare and in accordance with the objectives of Islam,; falah (prosperous in the world and the hereafter), and in accordance with the five main elements that must be maintained in Islam, namely hifz ad-din, hifz an. -nafs, hifz al-aql, hifz an-nasl, and hifz al-mall. Keywords: Islamic law, the role of women, family welfare. Abstrak: Partisipasi peran perempuan dalam dalam dunia kerja tidak hanya berkontribusi terhadap berubahnya pola fikir dan tatanan perekonomian suatu daerah, akan tetapi juga telah memberikan kontribusi yang besar terhadap kesejahteraan keluarga. Penelitian ini menggunakan metode analisis deskriptif untuk menganalisis dan mendiskripsikan peran perempuan dalam peningkatan kesejahteraan ekonomi keluarga perspektif maqashid syariah. Berdasarkan dari hasil penelitian, ditemukan implikasi bahwa peran perempuan sangat positif dalam meningkatkan kesejahteraan keluarga dan sesuai dengan tujuan Islam yaitu falah (sejahtera dunia dan akhirat), serta sesuai dengan lima unsur pokok yang harus dijaga dalam islam, yakni hifz ad-din, hifz an-nafs, hifz al-aql, hifz an-nasl, dan hifz al-mall. Kata-kata kunci: hukum Islam, peran perempuan, kesejahteraan keluarga.